PRINSIP AMANAH SEBAGAI LANDASAN MANAJEMEN KINERJA PEGAWAI: STUDI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) YOGYAKARTA - Shendy Listya Wulandari; Siti Fatimah (JURNAL MANAJEMEN DAKWAH, 2022)
Islam is a universal religion regulates all aspects of life, including in the ritual and social fields. In Islam, work is seen as a divine vocation appropriate to human nature and as a means to achieve happiness in this world and the Hereafter. The principle of trust isÂ significant in Islamic teachings, emphasizing integrity, honesty,Â and responsibility at work. This study focuses on the implementation of the principle of trust in the performance of the State Civil Apparatus (ASN) at the Yogyakarta State Assets and Auction Service Office (KPKNL) in 2017. A qualitative research method was used by collecting data through interviews, observation, and documentation. The results of the analysis show that performance management at the Yogyakarta KPKNL involves planning, organizing, directing, controlling, measuring, and evaluating steps to improve organizational effectiveness and efficiency as well as ASN performance. The principle of trust is the main foundation by emphasizing integrity, honesty, reliability, responsibility and resource management. Performance evaluation is carried out using a "merit rating" system using the e-performance application. This research provides an in-depth understanding of the application of the principle of trust in ASN performance management at the Yogyakarta KPKNL and has the potential to increase the understanding and application of this principle in similar agencies. Yogyakarta KPKNL will continue to improve its performance and provide quality services to the public whose implementation.